Slough House : London Rules - Book 5 - Herron, Mick (London, UK Baskerville JMP, 2018)
"Over at Slough House, the MI5 satellite office for outcast and demoted spies, the agents are struggling with personal problems: repressed grief, various addictions, retail paralysis, and the nagging suspicion that their newest colleague is a psychopath. Plus someone is trying to kill Roddy Ho. But collectively, theyre about to rediscover their greatest strength--that of making a bad situation much, much worse. Its a good thing Jackson Lamb knows the rules. Because those things arent going to break themselves"--Amazon.com.
Keywords: Great Britain. -- MI5 -- Officials and employees; Fiction; Intelligence service -- Great Britain; Fiction; Terrorism -- Fiction; Political campaigns -- Fiction; London (England) -- Fiction; Thrillers (Fiction); Detective and mystery fiction